A prospective study on the role of centchroman in regression of fibroadenoma - Singla, Navdeep Kumar; Bhatia, Ruby; Verma, Renu; Bhatia, Suresh Kumar (International Surgery Journal, 2021)
Background: Fibroadenoma commonly present as painless breast lump in young girls. Nearly 10-15% regress spontaneously over the period of 6-60 months, rest are managed surgically. Centchroman (Saheli), a novel non-steroidal, selective anti-estrogen has been used for the treatment of mastalgia and its effectiveness in the treatment of fibroadenoma is being tested in the ongoing trials. Methods: A total of 60 patients between 15-35 years of age with painless lump breast of size 2 to 5 centimeters confirmed as fibroadenoma by fine needle aspiration cytology (FNAC) were included in the study. Detailed patient’s characteristics, clinical history, physical examination (for size in 2 dimensions), ultrasound findings (for size in 3 dimensions) were assessed. All participants included in the study were given tablet Centchroman (Saheli) 30 mg thrice weekly orally for 3 months. Size of Fibroadenoma was reassessed clinically for size in two dimensions and ultrasonologically for size in three dimensions at 4 weeks and 3 months of starting of therapy. Results: Out of 60 patients, 18 patients (30%) had complete response, 40 patients (66.66%) showed a decrease in the size of fibroadenoma and only 2 patients (3.33%) had no response to this therapy. None showed an increase in size. Conclusions: It may prove to be the most effective modality for the treatment of small sized fibroadenoma breast especially in unmarried girls with minimal side effects. Ultrasonology may be relied upon for follow up measurements since it is more accurate in measuring the dimensions.